2018
DOI: 10.1016/j.ijrobp.2018.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Hypoxic Tumors to Radiation Therapy Using Ultrasound-Sensitive Oxygen Microbubbles

Abstract: Our findings demonstrate the potential advantages of ultrasound-triggered oxygen delivery to solid tumors and warrant future efforts into clinical translation of the microbubble platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 38 publications
(42 reference statements)
1
86
0
Order By: Relevance
“…In addition, the interaction of NO with dissolved oxygen and the rapid degradation of NO made the assessment of the passive release profile challenging. MB stabilized with other types of shell materials, such as polymers (McEwan et al, 2014), dextran (Cavalli et al, 2009a), surfactants (Eisenbrey et al, 2015;Eisenbrey et al, 2018), or chitosan (Cavalli et al, 2009b) shells, may increase the timescale of gas diffusion across the shell, with or without the addition of osmotic gases for payload stabilization. The efficacy and biocompatibility of such agents for encapsulating NO could also be compared to lipid-shelled MB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the interaction of NO with dissolved oxygen and the rapid degradation of NO made the assessment of the passive release profile challenging. MB stabilized with other types of shell materials, such as polymers (McEwan et al, 2014), dextran (Cavalli et al, 2009a), surfactants (Eisenbrey et al, 2015;Eisenbrey et al, 2018), or chitosan (Cavalli et al, 2009b) shells, may increase the timescale of gas diffusion across the shell, with or without the addition of osmotic gases for payload stabilization. The efficacy and biocompatibility of such agents for encapsulating NO could also be compared to lipid-shelled MB.…”
Section: Discussionmentioning
confidence: 99%
“…However, future large animal and human studies (in which the recirculation time is longer) will be necessary to assess whether intravenous administration of Xe-OFPloaded microbubbles provides neuroprotection during ischemia. Recent reports with microbubbles stabilized with surfactants [28,62], dextran [63], polymer [64], or chitosan shells [65] show promise for reducing gas diffusion across the shell, even without co-encapsulating perfluorocarbon gases. In the future, the performance and biocompatibility of such agents should be compared against lipid-shelled microbubbles for Xe delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 34% of the Xe-ELIP payload exists in dissolved form in the lipid bilayer [17], which enables a biphasic release profile [19]. Shelled microbubbles have been investigated for the delivery of bioactive gases such as oxygen, nitric oxide, and hydrogen sulfide [24][25][26][27][28][29]. The volume of microbubbles is almost entirely composed of gas, which enables ultrasound-triggered release and enhancement of payload delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Fix et al showed that intra-tumoral injection lipid-coated OMB Ivyspring International Publisher can increase tumor oxygen levels and tumor control in a fibrosarcoma rat model [4]. In the same year, Eisenbrey et al showed that intravenous injection of surfactant-coated OMB can increase tumor oxygen and control in a breast cancer model [5,6]. These studies have demonstrated the promise of ultrasound-guided OMB for treating hypoxic tumors.…”
Section: Introductionmentioning
confidence: 99%